Copper resource demand prediction for low-carbon transition of China’s power system - Min, HAO; Peng, WANG; Weiqiang, CHEN (Zi yuan ke xue, 2025)
[Objective] Copper, as a critical strategic mineral resource, plays a pivotal role in the low-carbon energy transition of the power sector and the process of carbon neutrality. China is a country with a shortage of copper resources. Scientifically predicting the future demand and scrap generation of copper resources in the power system holds significant strategic importance for ensuring national copper resource security and optimizing resource recycling systems. [Methods] Based on the internationally recognized Integrated Policy Assessment Model (IPAM) under the global warming scenarios of 1.5 °C and 2 °C, as well as China’s “dual carbon” scenario and the dynamic material flow analysis method, this study estimated the in-use stock, demand, theoretical scrap volume, and degree of external dependence of copper in China’s power system from 1950 to 2050. [Results] (1) China’s installed power generation capacity was projected to increase from 1.85 million kW in 1950 to 5.4-6.0 million kW by 2050. The share of renewable energy generation was expected to increase with policy stringency, reaching 80% in the 1.5 °C scenario, 73% in the “dual carbon” scenario, and 67% in the 2 °C scenario by 2050. (2) By 2050, the in-use stock, demand, and theoretical scrap volume of copper in China’s power system were projected to reach 140-160 million tons, 6.5-8.1 million tons, and 4.0-4.8 million tons, respectively, representing an increase of approximately 3 times, 1.5 times, and 10 times compared to the levels in 2022. (3) In the 1.5 °C global warming scenario, China’s power system showed the highest copper demand, stock, and theoretical scrap volume, followed by China’s “dual carbon” scenario. (4) China’s degree of external dependence on copper resources showed a significant downward trend. In the 1.5 °C global warming scenario, it was projected to decline from 70% in 2023 to 48% by 2050, while it was expected to decrease further to 40% in the “dual carbon” scenario. In contrast, in the 2 °C global warming scenario, the dependence was projected to decrease to 38%. [Conclusion] China’s low-carbon power transition will significantly increase copper demand. The utilization of recycled copper can reduce the degree of external dependence, but short-term supply risks remain. It is recommended to strengthen resource exploration, recycling, and supply-demand assessment to ensure copper resource security.